2018
DOI: 10.21608/jappmu.2018.41098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Propolis Ethanolic Extract Supplementation to Ram Semen Extenders on Sperm Characteristics, Lipid Peroxidation and some Enzymatic Activities in Seminal Plasma in Chilled Semen

Abstract: This study designed to examine effects of adding different concentrations of propolis ethanolic extract (PEE) as antioxidant to ram semen extenders; tris egg yolk (TEY) or tris-soybean lecithin (TSBL) on sperm characteristics, lipid peroxidation and enzymatic activities in seminal plasma of ram semen preserved at 5°C for 48 hours. Semen was collected from five adult Rahmani rams using an artificial vagina twice/week for 5 weeks. Pooled semen was extended with TEY or TSBL supplemented with different concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 55 publications
6
10
1
Order By: Relevance
“…The viability data did not show superiority for the samples with propolis. This result is in accordance with El-Harairy et al (2018), which they reported the effect of propolis only on the increase in motility, with no improvement in the viability and integrity of biological membranes. In contrast, the best response of P1 and P2 groups to hiposmotic test, especially this latter, (El-Seadawy et al, 2017;Kasiotis et al, 2017;Baykalir et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The viability data did not show superiority for the samples with propolis. This result is in accordance with El-Harairy et al (2018), which they reported the effect of propolis only on the increase in motility, with no improvement in the viability and integrity of biological membranes. In contrast, the best response of P1 and P2 groups to hiposmotic test, especially this latter, (El-Seadawy et al, 2017;Kasiotis et al, 2017;Baykalir et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…This study result finding broadly supports the work of other studies in this area linking motility with source of energy and production of ATP which our result showed increased significantly in the general and progressive motility in addition of aqueoussemen extender as showed in Figure (1 and 2). Moreover, the figures illustrated the superiorityof G1 significantly among all groups, This study supports evidence from previous observations (Alenezy et al, 2019;Asadzadeh et al, 2021 andEl-Harairy et al, 2018) uses of natural source of material in the extender of semen for chilling and cryopreservation of the bull sperm, in the seam area the current study found that used of vitamins are promote and increased sperm parameter (general and progressive motility) is support our result (Espina et al, 2021). Also the season in Iraq had a significant effect upon animal testis specially the summer season which show the lowest reproductive activity (Ibrahim and Zaid, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…The percentages of progressive sperm motility in the four diluents were under the requirements of SNI 4869-1:2017 for frozen bovine semen, with sperm motility of at least 40% (Badan Standardisasi Nasional, 2017). Khalil et al (2018) reported that freezing and thawing processes decreased bull-sperm motility by 26.2%-60%. This study showed that the decreases in sperm motilities were between 3.6% and 28.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Low release of AST enzyme from the sperm reflects the effectiveness of the diluent in maintaining the integrity of the sperm membrane. Generally, the best semen diluents can block the release of enzymes and other electrolytes from the sperm cells (El-Harairy et al, 2018).…”
Section: Tasj-36996mentioning
confidence: 99%